Developments in virus-like particle-based vaccines for infectious diseases and cancer. (November 2011) - Buonaguro, Luigi; Tagliamonte, Maria; Tornesello, Maria Lina; Buonaguro, Franco M
Virus-like particles hold great promise for the development of effective and affordable vaccines. Indeed, virus-like particles are suitable for presentation and efficient delivery of linear as well as conformational antigens to antigen-presenting cells. This will ultimately result in optimal B-cell activation and cross-presentation with both MHC class I and II molecules to prime CD4 + T-helper as well as CD8 + cytotoxic T cells. This article provides an update on the development and use of virus-like particles as vaccine approaches for infectious diseases and cancer.